Unprotected time of early adolescence and intergenerational relations: a new educational issue - Pierpaolo Donati (Estudios sobre Educación, 2018)
The paper was given on 26 october 2001 at the international congress on “unprotected time of young people in the EU”, held at the University of Bologna (Italy). It discusses the social problems connected to the time in which young people (10-15 years) are unprotected by the socialising agencies in everyday life. The policies designed so far in eu countries to combat these problems are analysed and evaluated. The author underlines the fact that time is not equal for all generations, because time undergoes very differing accelerations and decelerations depending on the position of each generation and therefore it acquires a very different value and meaning for each of them. For these reasons, to pose the problem of unprotected time for young people means entering into the problem of how the various generations live their own time and the time for relating with other generations. The paper ends by suggesting some proposals for EU educational policies.